Inovasi Layanan Drive Thru “Peminjaman dan Pengembalian Buku” di Balai Layanan Perpustakaan DPAD Daerah Istimewa Yogyakarta - Meyza Indriyani; Labibah Zain (Universitas Wijaya Kusuma Surabaya, 2023)
Purpose Research. This research was conducted to determine the innovation of the drive thru service